Pengembangan Keberagamaan Siswa Melalui Program Keagamaan di Sekolah Menengah Pertama - Irma Ni’matul Jannah; Andewi Suhartini (PUSTAKA: Jurnal Bahasa dan Pendidikan, 2024)
Education plays a crucial role in shaping the character and morality of the younger generation. This article highlights the important role of schools as a place of knowledge transfer as well as a process of character building. The problem of morality among students is the main focus, with an emphasis on developing students' religiosity as a potential solution. Various religious programs, including Qur'an memorization evaluation, joint prayers, and other routine activities, are the main strategies in improving student morality. The qualitative research method uses a phenomenological approach to describe the experience of awareness in developing students' religiosity. The results show the school's commitment in improving students' morality through well-planned and implemented programs. The whole article emphasizes the important role of education in shaping students' character and provides a concrete picture of the school's efforts in improving morality through the development of religiosity.